已知a,b,c为三个非零实数,且a+b+c=0求证:[(a-b)⼀c+(b-c)⼀a+(c-a)⼀b][c⼀(a-b)+a⼀(b-c)+b⼀(c-a)]=9

2025-02-26 01:28:36
推荐回答(3个)
回答1:

因为a+b+c=0,所以c=-a-b,
所以(a-b)/c+(b-c)/a+(c-a)/b=(a-b)/(-a-b)+(b+a+b)/a
+(-a-b-a)/b=(b-a)/(b+a)+2b/a-2a/b,
通分,得(a-b)/c+(b-c)/a+(c-a)/b=(2b^3+3ab^2-3a^2b-2a^2)/[(a+b)ab]=(2b+a)(b+2a)(b-a)/[(a+b)ab].
而c/(a-b)+a/(b-c)+b/(c-a)=(b+a)/(b-a)+a/(2b+a)-b/(2a+b),
通分,得c/(a-b)+a/(b-c)+b/(c-a)=9ab(a+b)/[(2b+a)(b+2a)(b-a)],
所以[(a-b)/c+(b-c)/a+(c-a)/b][c/(a-b)+a/(b-c)+b/(c-a)]=9.

回答2:

因为a+b+c=0,所以c=-a-b,
所以(a-b)/c+(b-c)/a+(c-a)/b
=(a-b)/(-a-b)+(b+a+b)/a+(-a-b-a)/b
=(b-a)/(b+a)+2b/a-2a/b
通分,得(a-b)/c+(b-c)/a+(c-a)/b
=(2b^3+3ab^2-3a^2b-2a^2)/[(a+b)ab]
=(2b+a)(b+2a)(b-a)/[(a+b)ab].
而c/(a-b)+a/(b-c)+b/(c-a)=(b+a)/(b-a)+a/(2b+a)-b/(2a+b)
得c/(a-b)+a/(b-c)+b/(c-a)=9ab(a+b)/[(2b+a)(b+2a)(b-a)],
则[(a-b)/c+(b-c)/a+(c-a)/b][c/(a-b)+a/(b-c)+b/(c-a)]=9.

回答3:

98